Revised Outlook for Remittance Flows 2009‐2011 : Remittances Expected to Fall by 5 to 8 Percent in 2009 - Ratha, Dilip (World Bank, Washington, DC, 2012)
The authors have revised forecasts for remittance flows in the light of a downward revision to the World Bank's global economic outlook. The authors now expect a sharper decline of 5-8 percent in 2009 compared to earlier projections outlined in migration and development brief 8 (report no. 46715). This decline in nominal dollar terms is small relative to the projected fall in private capital flows or official aid to developing countries. However, considering that officially recorded remittances registered double-digit annual growth in the past few years to reach an estimated $305 billion in 2008, an outright fall in the level of remittance flows as projected now will cause hardships in many poor countries.